Current and future risks of asbestos exposure in the Australian community. (1st October 2016) - Gray, Corie; Carey, Renee N.; Reid, Alison
Abstract : Background: Australia mined asbestos for more than 100 years and manufactured and imported asbestos products. There is a legacy of in situ asbestos throughout the built environment. Methods: The aim of this study was to identify the possible sources of current and future asbestos exposure from the built environment. Telephone interviews with environmental health officers, asbestos removalists, and asbestos assessors in Australia sought information about common asbestos scenarios encountered. Results: There is a considerable amount of asbestos remaining in situ in the Australian built environment. Potential current and future sources of asbestos exposure to the public are from asbestos-containing roofs and fences, unsafe asbestos removal practices, do-it-yourself home renovations and illegal dumping. Conclusion: This research has highlighted a need for consistent approaches in the regulation and enforcement of safe practices for the management and removal of asbestos to ensure that in situ asbestos in the built environment is managed appropriately.